Vulvovaginal atrophy in women after cancer. (2nd November 2019) - Cox, P.; Panay, N.
Abstract: The number of women surviving longer after a cancer diagnosis is increasing. This means that more awareness regarding their health is required. This review will focus on vulvovaginal atrophy (VVA)/genitourinary syndrome of menopause, one of the most distressing adverse iatrogenic effects of the menopause, secondary to cancer therapies. The cancer therapies themselves, such as radiotherapy, chemotherapy, and surgery, have a direct impact on the lower genital tract which interplays with the ensuing hypoestrogenic state of the menopause. Symptoms of VVA are still under-reported and undertreated as neither clinicians nor patients are forthcoming in discussing the problem, despite its profound negative impact on quality of life. In terms of treatment of VVA, this review will look at the use of various options, including estrogen post cancer diagnosis, as well as considering newer emerging therapies such as dehydroepiandrosterone, ospemifene, and laser. The care of a woman post cancer diagnosis should be a multidisciplinary responsibility. However, further research is required into emerging treatment options as well as long-term safety data, to ensure all health-care providers and women are fully informed and confident to effectively address the impact of VVA post cancer diagnosis.